Credit Growth in Indonesia: Comparison Between Government Banks and Private Banks Through the Chow Test - Salmita, Dewi; Al Khazaleh, Salameh; Syamsu, Nur; A Rifai, Rachmawati (Iqtishodia: Jurnal Ekonomi Syariah, 2025)
The aim of this research is to analyze the factors that influence credit growth in government banks and private banks consisting of NPL, CAR and BOPO. The sample for this research was 7 government banks and 26 private banks listed on the Indonesian stock exchange from 2014-2023. Data analysis in this study used multiple regression analysis and chow test. The results of the study show that NPLs have a significant negative influence on credit growth in both types of banks, with a stronger influence on government banks. CAR has a positive effect on credit growth at private banks, but does not have a significant effect at government banks. Meanwhile, BOPO has no effect on credit growth in both types of banks. This difference reflects different risk management strategies and credit policies between government and private banks, where government banks tend to be more conservative in credit expansion when NPLs increase, supported by the government's significant role in supporting capital stability.